2019
DOI: 10.3389/fmicb.2019.01388
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing and Variations in Amount of tst Gene Expression of TSST-1-Producing Clinical Staphylococcus aureus Isolates

Abstract: The toxic shock syndrome toxin-1 (TSST-1), encoded by tst gene, has been proposed to cause staphylococcal toxic shock syndrome (TSS) in a susceptible host, which highlights the need to evaluate the level of tst gene expression and molecular genetic characteristics of the tst -positive isolates. A total of 916 S. aureus isolates collected from seven hospitals in China were screened for the tst gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
(57 reference statements)
1
18
0
Order By: Relevance
“…The sea gene is the most commonly associated source of foodborne poisoning in humans due to improper handling and storage (Chen et al 2018) and cases of subclinical mastitis in cattle (Fursova et al 2018). The toxic shock syndrome toxin-1 (TSST-1), which is encoded by the tst gene, is a significant virulence factor in S. aureus infections which can trigger excessive and nonconventional T-cell activation and cytokines release and consequently interfere with the immune system function systemically (Zhao et al 2019). Moreover, the tst gene can cause food poisoning in humans (Pérez et al 2020).…”
Section: Virulence Marker Genesmentioning
confidence: 99%
“…The sea gene is the most commonly associated source of foodborne poisoning in humans due to improper handling and storage (Chen et al 2018) and cases of subclinical mastitis in cattle (Fursova et al 2018). The toxic shock syndrome toxin-1 (TSST-1), which is encoded by the tst gene, is a significant virulence factor in S. aureus infections which can trigger excessive and nonconventional T-cell activation and cytokines release and consequently interfere with the immune system function systemically (Zhao et al 2019). Moreover, the tst gene can cause food poisoning in humans (Pérez et al 2020).…”
Section: Virulence Marker Genesmentioning
confidence: 99%
“…The nowadays-reports refer to increasing the worldwide distribution of the tst-1 gene to even higher levels than the already known elevated spreading 15 . It has been found that this gene has genetic variations which might suggest different virulence levels 16 .…”
Section: Discussionmentioning
confidence: 99%
“…As these toxins are present on mobile genomic elements, these can easily be horizontally transferred to other non-virulent strains (Varshney et al 2009). SEs (A-E) are termed as classic enterotoxins, except SEF which is superantigen TSST-1 due to its sequence and structural homology to toxic shock syndrome toxin (Zhao et al 2019).…”
Section: Staphylococcus Aureusmentioning
confidence: 99%